Mediator role of psychological resilience between post-traumatic stress symptoms and burnout in academicians affected by the earthquakes in Türkiye - Yetkin Tekin, Ayşegül (Frontiers in Psychology, 2024)
Purpose: This study aims to investigate the mediator role of psychological resilience in the relationship between post-traumatic stress and burnout symptoms in academicians affected by two earthquakes that occurred on February 6, 2023, affecting 11 provinces of Türkiye.The research sample consisted of 175 academicians affected by these earthquakes.Each academician completed an online survey consisting of a sociodemographic form, the PTSD Checklist for DSM-5 (PCL-5), the Brief Psychological Resilience Scale, and the Burnout Syndrome Inventory-Short Version.Results: Negative relationships were found between the post-traumatic stress symptom and burnout levels of academicians and their psychological resilience levels. Psychological resilience had a partial mediating role in the relationships of post-traumatic stress symptoms (reexperiencing, avoidance, and hyperarousal) and burnout.It can be said that higher post-traumatic stress symptoms' severity is associated with higher levels of burnout, and psychological resilience has a mediator role in the relationship between post-traumatic stress and burnout in earthquake-affected academicians.